A Training on TOEFL Strategies to Enhance Teachers’ Career for English Teacher Forum in Jambi City - Ratnaningsih, Paskalina Widiastuti; Masgo; Syafri, Rista Aldilla; Mery; Prasasti, Laura (⁠International Journal of Asia Pacific Community Service, 2025)
This study aims to give training on TOEFL strategies for English teachers in English Teacher Forum (MGMP). The training is given for English Teacher Forum of junior high school in Jambi city. The training on TOEFL strategies is needed to enhance teachers’ career. This study used training and survey approach. The training was related to the strategies of taking the TOEFL test. It includes the strategies of Listening, Structure, and Reading in TOEFL. The survey used questionnaire to discover participants’ perceptions of the training. The results showed that the training was beneficial for the English teachers of junior high school in English Teacher Forum. They were able to understand TOEFL strategies. For further study, it is recommended to conduct another training of TOEFL with deeper understanding. Hence, it can enhance more knowledge on TOEFL.